PUBLIC RELATIONS DI INDONESIA DITINJAU DARI PERSPEKTIFKARIR DAN PROFESIONALISME - Richardo, Freddy (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2010)
Title of paper "Public Relations in Indonesia viewed from the perspective of Career and Profession" identical with the Public Relations Public Relations (PR). This article addressing the tendency of leaders, executive in government and enterprise organizations understand the function, role and duties of public relations as an in formation service, as well as complement the work unit, are inconsistent with the philosophy of PR is a twoway communication.The purpose of this writing intended to give advice for the role, functions and duties of Public Relations to serve as a future career position or profession in the field of communication, in establishing the relationship between the organization/institution with the public (stakeholders) through twoway communication, so that in the same time,   are both getting benefits for both parties.The methodology used in collecting data in this paper, first,  conducted from various sources directly from the field by requesting information directly from some PR practitioners in government and private institutions. Second, supported by secondary data, in the form of literature that is relevant with the title of this paper.Through this paper, expected future associations engaged in the PR I Public Relations can develop the role functions and duties of public  relations as a career job,  other than as a profession with special position in society because they make relationships based on trust, do work that is considered highly valuable, have the necessary expertise and knowledge.